Oral motor praxis in individuals with autism spectrum disorders in the context of modern speech and language therapy - Kateřina Vitásková; Alena Říhová (Social Welfare: Interdisciplinary Approach, 2014)
The objective of the submitted contribution is to describe the issue of oral motor praxis in individuals with autism spectrum disorders (ASD). The initial section of the contribution deals with the theoretical solutions relating to the given issue and, concurrently, provides information on the already implemented research focused on the given issue. The central domain is the analysis of oral motor ability in children with ASD through the application of the partial task activity ‘Warm-up’ from the software programme FONO 2. The results of the longitudinal observation are detected through the created evaluation scale and are recorded in the form of tables and graphs that are, subsequently, analysed. The results of the study constitute partial solutions of the specific research project IGA (IGA 2014/2015 PdF 2014_016), which was implemented by the Institute of Special Education Studies of the Faculty of Education Palacký University in Olomouc (principal researchers: Kateřina Vitásková, Alena Říhová).